Interpretive Structural Modeling Approach to Civil Military Relations in India - Sharma , Dr. Sanjeev; Tapas, Dr. Poornima (Science and Technology - Recent Updates and Future Prospects Vol. 5, 2024)
Civil Military Relations (CMR) is a complex mix of explicit, implicit, traditions, precedence, evolutions, powers forming part of the social contract that underpins the country`s governance. The main players in civil military relations are the politicians, the civilian bureaucracy, the society and the Armed Forces. Various important factors that influence Civil Military Relations include the formation of a state, command and control of the armed forces, evolution of the political environment and relationship between the state & the society. The subject is of immense importance for a developing mature democratic state. There are a few factors known as CMR Enablers and Barriers (EBs), that affect CMR. The paper studies the basic relationships amongst the shortlisted EBs and understands the driver and driven EBs. Interpretive Structural Modeling (ISM) technique with Micmac Analysis was used to determine inter-se relationships between the EBs. Ultimately, how critical each factor is for the success of CMR was identified. Legacy, Leadership and National Interest were found to be the most critical EBs. Five other EBs were also identified though less critical but of importance in CMR. Future studies could quantify the framework obtained from the ISM model, using Analytical Hierarchy Process (AHP). Future research in this field could be carried out using the Analytical Hierarchy Process (AHP).